OPPORTUNITIES & CHALLENGES FOR INDUSTRIES, WORKERS, AND GOVERNMENT OF INDONESIA IN THE ASEAN ECONOMIC COMMUNITY IMPLEMENTATION - Sumantoro, Indra Budi (Prosiding International conference on Information Technology and Business (ICITB), 2015)
The ASEAN Economic Community (MEA) era hasarrived, but the echo is still not being a major concern,both for the majority of community nor the government ofIndonesia. Things are more political noise and feels lumpyalways happened all the time, rather than discuss anythingthat has to be prepared and conducted in the MEA era.This paper would like to remind again community andgovernment to do preparation in the era of MEA. Thispaper is in principle underlines that the opportunities andchallenges for the industries, workers, and government, asthe tripartite, is very important to be used as a foundationin drawing up action plans to face the era of MEA.KEY WORDS: Opportunities, Challenges, Industries,Workers, and Government.